Medication Safety Beyond the Hospital and Role of Pharmacists in Ambulatory Medication Safety Process - Alshakka, Mohammed; Hassali, Mohamed Azmi; Ali, Heyam; Abdulla, Aymen Saleh; Shankar, P Ravi; Basaleem, Huda; Ibrahim, Mohammed Izham Mohamed (Journal of Pharmacy Practice and Community Medicine)
Medication safety is one of the challenges which is in focus now-a-days, and various approaches to reduce the incidence of medication related problems and risks are ongoing. Most initiatives have concentrated on medication safety in the hospital setting considering the increased risks of medication errors in hospitals. However, there are various factors and areas to be addressed regarding medication safety beyond the hospital setting. Although, attitudes towards medication use are changing among the public and health providers but, still the use of medicines beyond hospital settings requires more attention. Great efforts are needed in this area, due to diversity in the types of errors, the relationship between the provider and the patient, information transfer, optimization of e-prescribing systems, the lack of adequate training in analyzing the collected data and poor practical strategies for maintaining accurate medication lists in electronic medical records. Recently individuals have started becoming aware of the risks of patients’ medication exposure, however, still the area of medication safety beyond the hospital setting needs comunity pharmacy intervention to avoid malpractice claims and misled decisions in solving medication safety-related problems in the outpatient setting . All these approches will help in identify and prompt the detection of errors, open productive discussions, quality control checks, and effective wise system based decisions, and subsequently reduce the harm and risks before patient is exposed to any form of medication
Keywords: Drug safety; ADRs reporting; Ambulatory care; Role of pharmacists